Amyloidosis of the respiratory system: 16 patients with amyloidosis initially diagnosed ante mortem by pulmonologists. Issue 3 (27th July 2020) - Yamada, Masami; Takayanagi, Noboru; Yamakawa, Hideaki; Ishiguro, Takashi; Baba, Tomohisa; Shimizu, Yoshihiko; Okudela, Koji; Takemura, Tamiko; Ogura, Takashi
Background: Ante mortem diagnosis of amyloidosis of the respiratory system is rare. Few data are available regarding clinical presentation, precursor proteins, diagnostic procedures, comorbidities, complications, and outcome. We assessed clinical features of a series of patients with amyloidosis of the respiratory system in two Japanese centres. Methods: Medical records of 16 patients with amyloidosis of the respiratory system were retrospectively analysed. Amyloid was diagnosed by polarisation microscopy using Congo red-stained tissue specimens and classified immunohistochemically. Results: Median patient age was 71 years, and median follow-up period was 5 years. Immunoglobulin light-chain (AL)-λ amyloidosis was found in eight and AL-κ in five patients. Two patients harboured wild-type transthyretin and one harboured serum amyloid A-derived amyloid. Five different forms of amyloidosis of the respiratory system were observed: nodular pulmonary amyloidosis (seven patients), diffuse alveolar-septal amyloidosis (five), mediastinal lymph node amyloidosis (three), tracheobronchial amyloidosis (one), and pleural amyloidosis (one). One patient had diffuse alveolar-septal amyloidosis and mediastinal lymph node amyloidosis. Three of five patients with diffuse alveolar-septal amyloidosis were diagnosed by transbronchial lung biopsy as having concurrent diffuse alveolar haemorrhage or pneumocystis pneumonia. Two of three patients with mediastinal lymph node amyloidosis were diagnosed by endobronchial ultrasound-guided transbronchial needle aspiration. Conclusions: Not only nodular pulmonary amyloidosis, diffuse alveolar-septal amyloidosis, and tracheobronchial amyloidosis but also mediastinal lymph node amyloidosis and pleural amyloidosis should be considered in the differential diagnosis of amyloidosis of the respiratory system. Useful diagnostic methods include transbronchial lung biopsy for diffuse alveolar-septal amyloidosis and endobronchial ultrasound-guided transbronchial needle aspiration for mediastinal lymph node amyloidosis. Not only nodular, diffuse alveolar-septal and tracheobronchial amyloidosis but also mediastinal lymph node and pleural amyloidosis should be considered in the differential diagnosis of amyloidosis of the respiratory system https://bit.ly/2ZfZcxo